2010
DOI: 10.1158/0008-5472.can-10-0489
|View full text |Cite
|
Sign up to set email alerts
|

HGF/c-Met Acts as an Alternative Angiogenic Pathway in Sunitinib-Resistant Tumors

Abstract: Molecular and cellular mechanisms underlying resistance/low responsiveness to antiangiogenic compounds are under extensive investigations. Both populations of tumor and stroma (nontumor compartment) seem to contribute in inherent/acquired resistance to antiangiogenic therapy. Here, investigating in vivo efficacy of sunitinib in experimental models resulted in the identification of tumors that were resistant/ sensitive to the therapy. Analysis of tumor protein lysates indicated a greater concentration of hepato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
209
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(217 citation statements)
references
References 37 publications
8
209
0
Order By: Relevance
“…Several studies have suggested that factors such as FGF2 or platelet-derived growth factor, produced by either cancer or stromal cells, can contribute to the onset of resistance ( 57 , 61 ). Shojaei and colleagues ( 62 ) have shown that HGF production by the tumor stroma can also contribute to resistance to treatment with sunitinib, a multikinase inhibitor targeting the VEGF pathway. Indeed, they found that resistant tumors displayed a greater concentration of HGF and a high MET expression level in endothelial cells.…”
Section: Non-cell-autonomous Role Of Met In Sustaining Resistance To mentioning
confidence: 99%
“…Several studies have suggested that factors such as FGF2 or platelet-derived growth factor, produced by either cancer or stromal cells, can contribute to the onset of resistance ( 57 , 61 ). Shojaei and colleagues ( 62 ) have shown that HGF production by the tumor stroma can also contribute to resistance to treatment with sunitinib, a multikinase inhibitor targeting the VEGF pathway. Indeed, they found that resistant tumors displayed a greater concentration of HGF and a high MET expression level in endothelial cells.…”
Section: Non-cell-autonomous Role Of Met In Sustaining Resistance To mentioning
confidence: 99%
“…Expression of both cMet and HGF is induced by hypoxiainducible factor 1a, further providing evidence for an important role of the HGF/cMet axis in adverse microenvironment conditions to promote tumour angiogenesis 14,15 . Importantly, it has been reported in a preclinical model that HGF/cMet signalling can act as an alternative angiogenic pathway in sunitinib-resistant tumours 16 . These observations indicate that targeting HGF/cMet signalling pathway in endothelial cells might be an effective approach to overcome the evasive resistance of cancer cells in the context of angiogenesis redundancy.…”
mentioning
confidence: 99%
“…We have reproducibly isolated c-MET CTCs from patients with metastatic, treatment-refractory RCC, gastroesophageal, and colorectal adenocarcinomas. Patients were selected for high tumor burdens and treatment refractoriness to VEGF or EGFR/HER2-based therapies, where c-MET may play a role in mediating resistance (14,20). Surprisingly, c-MET CTCs were not detected in the majority of patients, indicating that this assay may not detect c-MET overexpressing, nonamplified CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were enrolled for each of the following: prostate adenocarcinoma (10 patients), RCC (10 patients), colorectal adenocarcinoma (10 patients), urothelial carcinoma (8 patients), gastroesophageal adenocarcinoma (7 patients), and pancreatic adenocarcinoma (7 patients). Efforts were made to enroll patients with resistant disease to VEGF (RCC) or EGFR (colon) inhibitors, or for men with bone metastatic CRPC (prostate) to enrich for c-MET expression (13,14,20). All patients had metastatic disease with predominantly lymph node, liver, lung, and bone metastases (Table 1).…”
Section: C-met-expressing Ctcs In Patients Can Be Captured With the Cmentioning
confidence: 99%